Stomoxys calcitrans (Diptera: muscidae): means and methods of control. Overview - М. A. Levchenko; E. A. Silivanova (Российский паразитологический журнал, 2020)
The purpose of the research: to analyze and summarize literature data on the main means and methods of protecting animals from stable flies Stomoxys calcitrans and to reduce their number.Materials and methods. The analysis of literature data from foreign sources over the past 30 years describing the means and methods of controlling the numbers of S. calcitrans and ways to protect animals from their attack. Results and discussion. A literature review on the means and methods of controlling the abundance of S. calcitrans is presented. Chemicals are widespread and can be used to combat the pre-adult stages of development of flies by introducing them into the substrate or feeding animals, as well as to combat adult insects by treating surfaces or in traps. In the description of physical control methods, attention is paid to traps and various methods of attracting insects to them. As biological control methods for S. calcitrans, researchers are actively studying the possibilities and prospects of using parasitoids (for example, Hymenoptera, including four families and about ten species), more than ten species of ticks from different families, entomopathogenic nematodes (a species of Heterorhabditis bacteriophora), fungi and individual species bacteria.